2020
DOI: 10.3390/nano11010017
|View full text |Cite
|
Sign up to set email alerts
|

Gd/Y Hydroxide Nanosheets as Highly Efficient T1/T2 MRI Contrast Agents

Abstract: To develop highly efficient T1/T2 magnetic resonance imaging (MRI) contrast agents (CAs), Gd/Y hydroxide nanosheets were synthesized by a simple exfoliation method from layer compounds using sodium polyacrylate (PAA) as a dispersant and stabilizer. Transmission electron microscopy (TEM) and atomic force microscopy (AFM) results revealed the excellent performance of monolayer nanosheets with thicknesses of up to 1.5 nm. The MRI results of the T1 and T2 relaxation times showed that all of the Gd/Y hydroxide nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…[ 26,37 ] Generally, during the Stage 3 when the illumination is turned off, a significant reverse current peak occurs due to the built‐in potential generated by the pyroelectric effect (dT/dt < 0), as opposed to that of the heterojunction's built‐in electric field. [ 37,38 ] Notably, the device utilizing Ti 3 C 2 T x MXene‐based HTL effectively mitigates the reverse temperature difference potential through a robust built‐in electric field formed in the heterojunction, [ 24 ] thereby significantly eliminating this phenomenon. The response time is another crucial parameter for characterizing device performance.…”
Section: Resultsmentioning
confidence: 99%
“…[ 26,37 ] Generally, during the Stage 3 when the illumination is turned off, a significant reverse current peak occurs due to the built‐in potential generated by the pyroelectric effect (dT/dt < 0), as opposed to that of the heterojunction's built‐in electric field. [ 37,38 ] Notably, the device utilizing Ti 3 C 2 T x MXene‐based HTL effectively mitigates the reverse temperature difference potential through a robust built‐in electric field formed in the heterojunction, [ 24 ] thereby significantly eliminating this phenomenon. The response time is another crucial parameter for characterizing device performance.…”
Section: Resultsmentioning
confidence: 99%
“…By studying different Gd doping ratios, it was found that the structure of 10% Gd nanosheets was the most conducive to MRI. 131 When the two Gd 3+ ions in the nanosheets were exactly separated by two Y 3+ ions, each Gd 3+ ion in a relatively short distance (1.3 nm) will contact the most water molecules, which could achieve excellent T 1 – T 2 dual-mode MRI performance. The nanosheets prepared by a top-down stripping method could obtain high crystal quality, less defects, and excellent physical and chemical properties.…”
Section: Engineered Nanomaterials With Various Shapes For Dual-mode M...mentioning
confidence: 99%
“…T 1 -Based MRI contrast agents could reduce the T 1 relaxation time, resulting in higher signal intensities in T 1 -weighted MR images and thus T 1 contrast agents are called “positive contrast agents”. 69 Mn( ii ) 70 and Gd( iii ) 71 are the most common MR contrast agents, thus improving proton relaxation and leading to high signals in T 1 -weighted imaging. 70 The T 1 relaxation rate depends on the spin quantum number ( S ) and is inversely proportional to the distance between the metal ion and the water proton.…”
Section: Mno2 For Magnetic Resonance Imagingmentioning
confidence: 99%